The discourse of Friday sermon in Surakarta; A socio-pragmatic study - Saddhono, Kundharu (UI Scholars Hub, 2012)
This research aims to explain the Friday sermon by analysing the structure of its discourse, the selection and composition of its topics, the form and functions of its codes and code switching, the form of its speech acts, and the characteristics of its language and specific terms. The method used is descriptive and qualitative. This research considers the speech components of the sermon and approaches it contextually. The analysis of the speech acts is based on Kreidler's theory (1998), while that of the characteristics of the language is based on the Dell Hymes's theory. The data were collected in Surakarta and several of its mosques assuming the representativeness of the city and the location of the mosques. The analysis and presentation of the data have led to the following conclusions: the Friday sermon contains oral discourse which has regular and typical structure; the strategies of the composition of the topics include quotation, storytelling, and use of popular expressions; the forms of the codes and code switching involve Arabic, Indonesian, Javanese, and English languages; the utterances of the sermon contain all forms of speech acts; various terms appear in the sermons indicating that the Friday sermon functions as a register or usage of language in a particular field